Genetic aspects of antibiotic induced deafness: mitochondrial inheritance. Issue 2 (February 1991) - Hu, D N; Qui, W Q; Wu, B T; Fang, L Z; Zhou, F; Gu, Y P; Zhang, Q H; Yan, J H; Ding, Y Q; Wong, H
Abstract : Analysis of 36 pedigrees with a positive family history of aminoglycoside antibiotic induced deafness, ascertained in a population of 483, 611 in Zhabei District in Shanghai, showed that the susceptibility to antibiotic ototoxicity was transmitted by females exclusively, indicating mitochondrial inheritance. Reanalysis of 18 other published pedigrees confirmed this conclusion.